The development of a measurement instrument to measure the quality of internet investor relations - G. F. Nel; L. M. Brummer (South African Journal of Business Management, 2016)
The purpose of this study was to develop a measurement instrument to measure the quality of Internet investor relations (IIR). This study will aid future research to examine IIR and provide guidance to companies in the development of an IIRstrategy. The development of the instrument was based on best practice guidelines Issued by the Investor Relations Society, an extensive literature review and a pilot study. The result was a measurement instrument that consists of 346 attributes.Quality is assessed by measuring content as widely as possible, by including attributes to measure the accessibility, navigation and timeliness of information, and by allowing for the measurement of attributes as being partially availablebased on breadth, usability and timeliness considerations. The reliability and validity of the measurement instrument was confirmed on the basis of the measurement results of a sample of 85 JSE-listed companies.
Keywords: 650